2020
DOI: 10.1302/2058-5241.5.180106
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of tarsal coalitions in children and adolescents

Abstract: A tarsal coalition is an abnormal connection between two or more tarsal bones caused by failure of mesenchymal segmentation. The two most common tarsal coalitions are calcaneonavicular coalition (CNC) and talocalcaneal coalition (TCC). Both CNC and TCC can be associated with significant foot and ankle pain and impaired quality of life; there may also be concomitant foot and ankle deformity. Initial, non-operative management for symptomatic tarsal coalition commonly fails, leaving surgical intervention as the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 53 publications
0
25
0
10
Order By: Relevance
“…A historical report from Mitchell and Gibson, who undertook resection without interposition, demonstrated a recurrence rate of 66% (1) . In response to those results, Mubarak et al (14) conducted a retrospective study that found good results using autogenous fat as an interposition graft, showing lower rates of reossification and reoperation compared with the use of extensor digitorum brevis as interposition graft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A historical report from Mitchell and Gibson, who undertook resection without interposition, demonstrated a recurrence rate of 66% (1) . In response to those results, Mubarak et al (14) conducted a retrospective study that found good results using autogenous fat as an interposition graft, showing lower rates of reossification and reoperation compared with the use of extensor digitorum brevis as interposition graft.…”
Section: Discussionmentioning
confidence: 99%
“…Tarsal coalition is a term used to define an abnormal connection between two tarsal bones, was officially described for the first time by Buffon in 1796, and is caused by failure of mesenchymal segmentation during embryogenesis (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Given the fibrous attachment on the fragment we found during surgery a fracture secondary to fibrous calcaneonavicular coalition is highly probable. Few open or miniopen techniques are described to remove the calcaneonavicular coalition [10]. Arthroscopy is an attractive method given the minimisation of the articular instability of the midfoot joint secondary to surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…7 La afectación de la faceta posterior fue estimada para decidir si la barra era resecable de acuerdo al protocolo utilizado en nuestro servicio. 1 En aquellos pacientes que presentaban una coalición que afectaba menos de 50% de la faceta posterior se indicó resección de la misma. Si el AAC era mayor a 16 grados se indicó realineación asociada.…”
Section: Materials Y Métodosunclassified
“…Las coaliciones tarsales representan una anomalía congénita en la cual existe una fusión fibrosa, cartilaginosa u ósea entre dos o más huesos del tarso. 1 La incidencia estimada en la población es de 1 a 6%; las más frecuentes son las localizadas entre el calcáneo-escafoides tarsiano y astrágalo-calcáneo (aproximadamente 90% de los casos reportados). 2,3 Un alto porcentaje de los pacientes que presentan esta patología suelen requerir tratamiento quirúrgico para aliviar el dolor, mejorar la movilidad o corregir la deformidad asociada.…”
Section: Introductionunclassified